Disabilitas Intelektual: Masalah dan Penyelesaiannya dalam Pembelajaran IPS di Kota Singaraja (Studi Kasus di SMP Negeri 5 Singaraja) - Ni Nyoman Yuni Kariyani; I Wayan Lasmawan; I Wayan Kertih (Universitas Hamzanwadi, 2026)
Inclusive education demands an equitable system for all learners, including students with intellectual disabilities who frequently face difficulties in Social Studies (IPS) due to its abstract concepts. This study aims to identify learning difficulties, analyze teachers' adaptive strategies, map obstacles, and describe the success of interventions in Social Studies learning. This qualitative research applied a holistic-integrative case study design at SMP Negeri 5 Singaraja. Data were gathered through in-depth interviews, observations, and document analysis, then analyzed using the Miles and Huberman interactive model. The primary challenges included limited attention span, difficulties in processing technical vocabulary, and challenges in understanding complex instructions. Teachers' adaptive strategies involved: (1) shifting from lectures to digital visual media (YouTube and TikTok); (2) simplifying the curriculum through content differentiation; and (3) implementing structural interventions through the Program Akselerasi Kecepatan dan Usaha Baca (PACU) in synergy with Undiksha students. The main obstacle was the time management dilemma between regular curriculum administration and intensive special needs assistance. The success of interventions was evidenced by reduced cognitive load, increased motivation, social independence, basic literacy, and solid collaboration with parents. The integration of visual media, material simplification, and systemic support (PACU program and university synergy) is proven effective in mitigating learning barriers and improving adaptive behavioral functions of intellectually disabled students.